2014
DOI: 10.1007/s11274-014-1625-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, anti-inflammatory and probiotic potential of Enterococcus hirae isolated from the rumen of Bos primigenius

Abstract: In the present study bacterial strains were isolated from the rumen fluids of Bos primigenius and investigated their in vitro probiotic properties with potent antibacterial activity and anti-inflammatory effects. 9 g positive bacterial isolates were obtained and three isolates could able to tolerate gastric conditions, high bile salt concentrations and exhibited significant bactericidal effect against the enteric pathogens Vibrio cholera, Enterococcus faecalis, Enterobacter aerogens, Pseudomonas aeruginosa, Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…Results of this study validated that E. hirae F2 was surviving bile salts from 0.2% to 1.0% concentration, which is 4–5 times higher than the bile salt concentration of human intestine. However, previous studies (Gupta & Tiwari, 2015; Selvaraj et al, 2014) on E. hirae also indicated similar kind of results of bile salt tolerance. Further confirmation related to bile salt tolerance of E. hirae F2 was confirmed by the presence of BSH enzyme.…”
Section: Discussionsupporting
confidence: 73%
“…Results of this study validated that E. hirae F2 was surviving bile salts from 0.2% to 1.0% concentration, which is 4–5 times higher than the bile salt concentration of human intestine. However, previous studies (Gupta & Tiwari, 2015; Selvaraj et al, 2014) on E. hirae also indicated similar kind of results of bile salt tolerance. Further confirmation related to bile salt tolerance of E. hirae F2 was confirmed by the presence of BSH enzyme.…”
Section: Discussionsupporting
confidence: 73%
“…While the specific mechanism of this observation was not established by this study, others have shown that the lipoteichoic acid of E. hirae is able to protect against loss of epithelial tight junction function induced by TNF-α (Miyauchi et al, 2008). Additionally, E. hirae can limit the secretion of inflammatory mediators induced by LPS (Arokiyaraj et al, 2014; Miyauchi et al, 2008) and exerts bactericidal effects against numerous pathogens including E. coli and E. faecalis (Miyauchi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma cell line HT-29 was obtained from NCCS (National Centre for Cell Sciences), Pune, India and maintained in Dulbecco's modified Eagle's medium (DMEM, Himedia), with 10% fetal bovine serum (Himedia), 1X antibiotic-antimycotic solution (Himedia). Adhesion studies on HT-29 cells were performed as described by Arokiyaraj et al (2014). After incubation, the bacterial suspensions were removed carefully; stained with Giemsa stain for 20 min at room temperature followed by methanol fixation, and visualized under inverted microscope.…”
Section: Adhesion To Human Adenocarcinoma Cell Line Ht-29mentioning
confidence: 99%